SOIL EROSION AND ROUTES OF USE AND PRODUCTION IN THE MATOPIBA REGION, BRAZIL - Ferraz-Almeida, Risely; Urenha Silva, Caroline; Ribeiro, Felipe Rezende de Moura (REVISTA DE AGRICULTURA, 2023)
The goal was to monitor the production and soil erosion in the “MATOPIBA” region in the last 20 years. The study monitored agricultural production in the Brazilian Savanna, situated in the States of Tocantins (TO), Maranhão (MA), Bahia (BA), and Piauí (PI). The results showed that soybean occupies the largest area, corn and cotton show oscillations and coffee and sugar cane remain with values without major changes. In the production routes, the production areas present a positive correlation with k-apexes higher than 0.60 (p<0.05), indicating there is an increase in areas and no negative influence between the crops. The highest average erosivity rates were found respectively in the states of Tocantins and Maranhão. Conclude that the region MATOPIBA presents great potential for Brazilian agriculture requiring private and public actions to make sustainable use of the region through advanced technologies with conservation systems to avoid soil and water losses.